Adoption of processing technologies and innovative food preservation techniques: findings from smallholders in the Lindi Region in Tanzania - Sarr, Malika; Majili, Zahra; Khalili, Niloofar; Matavel, Custodio E.; Mbwana, Hadijah A.; Kaingo, Jacob; Löhr, Katharina; Rybak, Constance (Frontiers in Sustainable Food Systems, 2024)
Adopting processing technologies and innovative food preservation is crucial for improving the food security and nutritional status of rural populations in Tanzania and other countries in the Global South. However, low adoption rates among smallholders highlight the need for a better understanding of farmers' decision-making processes. The aim of this study is to examine extrinsic and intrinsic factors influencing smallholders’ decision-making processes in the adoption of innovative food processing and preservation techniques (specifically, pigeon pea flour-based products, threshers, dehullers) in Mitumbati and Mibure in the Lindi Region in Tanzania. Primary data on 555 farm households were collected using a standardized survey. Extrinsic influential factors were analyzed using binary logistic regression analysis. The results on internal decision-making are based on an analysis of barriers and motivations identified by farmers in relation to the uptake of the different innovations. Training and awareness emerged as the most significant factors positively associated with the adoption of all innovative processing and preservation techniques. Moreover, the results show that the primary drivers for smallholders in the study region to adopt innovative technologies were the potential health benefits and time savings they offered. The main challenge they faced was a lack of knowledge about the innovations. The results indicate that disseminating knowledge is crucial for the successful adoption of innovative processing technology in the study region. Improving and expanding training programs to be more inclusive can help to create incentives and overcome barriers, leading to increased adoption.